1988
DOI: 10.1002/bit.260310210
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density culture of mouse–human hybridoma in serum‐free defined medium

Abstract: Mouse-human hybridoma 4H11 cells producing anti-Pseudomonas sp. monoclonal antibody (IgA) grew in a serum-free medium supplemented with insulin, transferrin, ethanolamine, and selenite (ITES). The hybridoma could be applied to high-density culture in a serum-free medium supplemented with ITES, 0.5% BSA, egg yolk VLDL, and artificial blood FC-43 in a culture vessel equipped with hollow-fiber modules for medium exchange. Total cell density reached 1.1 x 10(7) cells/mL (viable cell density was 7.6 x 10(6) cells/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…This result is consistent with the previous ones in which a lower plasma membrane fluidity was correlated with lower shear sensitivity. Takasawa et al 49 have found that addition of very low density lipoproteins (VLDL) to high density cultures of hybridomas can minimize cell damage caused by agitation. It is well known that VLDL readily transfer cholesterol into the plasma membrane of mammalian cells.48 Hence, it can be argued that the protective effect described by Takasawa et al 49 was possibly due to an increased cholesterol content in the cells which effectively decreased the PMF.…”
Section: Effect Of Cholesterolmentioning
confidence: 99%
“…This result is consistent with the previous ones in which a lower plasma membrane fluidity was correlated with lower shear sensitivity. Takasawa et al 49 have found that addition of very low density lipoproteins (VLDL) to high density cultures of hybridomas can minimize cell damage caused by agitation. It is well known that VLDL readily transfer cholesterol into the plasma membrane of mammalian cells.48 Hence, it can be argued that the protective effect described by Takasawa et al 49 was possibly due to an increased cholesterol content in the cells which effectively decreased the PMF.…”
Section: Effect Of Cholesterolmentioning
confidence: 99%
“…Also worthy of note here is that significant process improvement is most likely with perfusion type systems based on recent published work (e.g. Takazawa et al, 1988;Klerx et al, 1988). Table 6 summarises a few of the considerations to be made when evaluating cell culture systems for in vitro production of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…more ancillary equipment such as pumps, holding tanks and continuous centrifuges and thus more susceptible to contamination and a possible reduction of antibody specificity at low dilution rates (Harbour et al, 1988). Perfusion systems appear widely in the literature (e.g., Tharakan and Chau, 1986;Takazawa et al, 1988;Altshuler et al, 1986;Klerx et al, 1988;Reuveny et al, 1985Reuveny et al, , 1987Butler et al, 1983). Despite their obvious advantages there are problems associated with the high populations of non-viable cells due to mass transfer problems and operational problems such as sterility maintenance, arising during long production runs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, each charge can have a different ability for promoting cell growth and product formation. The use of a totally defined serum free medium can overcome this problem if it is possible to adapt the cells to this conditions without loss of productivity (Takazawa et al, 1988).…”
Section: Introductionmentioning
confidence: 99%